Prevention and Potential Treatment Strategies for Respiratory Syncytial Virus - Bo-Wen Sun; Peng-Peng Zhang; Zong-Hao Wang; Xia Yao; Meng-Lan He; Rui-Ting Bai; Hao Che; Jing Lin; Tian Xie; Zi Hui; Xiang-Yang Ye; Li-Wei Wang (Molecules, 2024)
Respiratory syncytial virus (RSV) is a significant viral pathogen that causes respiratory infections in infants, the elderly, and immunocompromised individuals. RSV-related illnesses impose a substantial economic burden worldwide annually. The molecular structure, function, and in vivo interaction mechanisms of RSV have received more comprehensive attention in recent times, and significant progress has been made in developing inhibitors targeting various stages of the RSV replication cycle. These include fusion inhibitors, RSV polymerase inhibitors, and nucleoprotein inhibitors, as well as FDA-approved RSV prophylactic drugs palivizumab and nirsevimab. The research community is hopeful that these developments might provide easier access to knowledge and might spark new ideas for research programs.